Metal ion hybridized degradable polyester as well as preparation method and application thereof

By introducing citrate metal salts in the preparation process of degradable polyester, metal ions were successfully hybridized into the polyester molecular chain, solving the problem of how to effectively introduce metal ions into degradable polymers, and promoting bone metabolism, mineralization and development.

CN119505190APending Publication Date: 2025-02-25GUANGDONG ZHENTAI BIOTECHNOLOGY CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411995249.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the preparation of degradable polymers, how to effectively introduce metal ions to promote bone metabolism, mineralization and development is a major challenge.

Method used

By polymerizing the degradable components in the presence of a catalyst and adding metal citrate salt to the reaction system, the polymer undergoes chemical reaction with the metal citrate salt, to prepare metal ion hybrid degradable polyester.

Benefits of technology

This method introduces citric acid structure and metal ions into the polyester molecular chain, improves biocompatibility, and provides a microenvironment conducive to bone health by regulating angiogenesis and bone tissue regeneration, and promotes bone metabolism, mineralization and development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505190A_ABST
    Figure CN119505190A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, in particular to metal ion hybridized degradable polyester as well as a preparation method and application thereof. The preparation method of the metal ion hybridized degradable polyester comprises the following steps: in the presence of a catalyst, carrying out polymerization reaction on degradable components at the temperature of 120-210 DEG C for 2-4 days to obtain a reaction system containing a polymer with the weight-average molecular weight of 1000-10000 Daltons, the degradable component comprises a degradable monomer and an initiator, or the degradable component comprises a degradable monomer pair; and adding a citric acid metal salt into the reaction system, and enabling the polymer and the citric acid metal salt to continue chemical reaction, so as to prepare the soluble metal ion hybridized degradable polyester. The prepared metal ion hybridized degradable polyester can be used as a bone phase filling material, a microenvironment beneficial to bone health is provided, metabolism, mineralization and development of bones are promoted, and a new choice is provided for the bone phase filling material with high biological activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of biomedical materials, and in particular to a metal ion hybridized degradable polyester and a preparation method and application thereof. Background Art

[0002] As one of the most important organs in the human body, bones mainly support the body shape. Bone filling is a technique to fill bones through injection or surgery, aiming to achieve the effects of repair, shaping or anti-aging by increasing the volume of bones, adjusting bone structure and improving the distribution of soft tissues.

[0003] Degradable polymers can be used as bone filling materials. Considering that bones are dynamic tissues, they are constantly undergoing the process of bone formation and bone resorption, which places high demands on the biological activity of degradable polymers. How to provide degradable polymers that are beneficial to bone metabolism, mineralization and development is an important topic. At the same time, in theory, many constant metal elements such as magnesium, as well as trace metal elements such as zinc and iron, are essential for the growth, development and function maintenance of bones. However, how to introduce metal ions in the preparation process of degradable polymers so that they can play the above functions has always been a great challenge. Summary of the invention

[0004] Based on this, the first aspect of the present application provides a method for preparing a metal ion hybridized degradable polyester, and its technical scheme is as follows:

[0005] A method for preparing a metal ion hybridized degradable polyester comprises the following steps:

[0006] In the presence of a catalyst, the degradable component is polymerized at a temperature of 120° C. to 210° C. for a time of 2 hours to 4 days to obtain a reaction system containing a polymer with a weight average molecular weight of 1000 Dalton to 10000 Dalton, wherein the degradable component comprises a degradable monomer and an initiator, or the degradable component comprises a degradable monomer pair;

[0007] Adding metal citrate into the reaction system, the polymer and the metal citrate continue to react chemically to prepare the soluble metal ion hybridized degradable polyester.

[0008] A second aspect of the present application provides a metal ion hybridized degradable polyester, which is prepared by the preparation method as described above.

[0009] The third aspect of the present application provides a bone filling material, which includes the metal ion hybridized degradable polyester as described above.

[0010] Compared with the traditional solution, this application has the following beneficial effects:

[0011] The metal ion hybridized degradable polyester of the present application is formed by chemically reacting a degradable monomer / initiator, or an oligomer obtained by polymerization of a degradable monomer pair with a metal citrate, and introducing a citric acid structure and a metal ion into the polyester molecular chain. After the citric acid structure is introduced into the polyester molecular chain, the obtained citric acid polyester structure has excellent biocompatibility, and its degradation product citric acid can participate in the tricarboxylic acid cycle of the organism, and is a structure with cell activity. In addition, metal ions can regulate angiogenesis and bone tissue regeneration through various pathways. The metal ion hybridized degradable polyester prepared in the present application can be used as a bone phase filling material, providing a microenvironment that is beneficial to bone health, promoting bone metabolism, mineralization and development, and providing a new choice for highly bioactive bone phase filling materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0013] Figure 1 This is the NMR spectrum of the oligomer before adding the metal citrate in Example 1;

[0014] Figure 2 This is the NMR spectrum of the manganese ion hybridized degradable polyester of Example 1;

[0015] Figure 3 This is the NMR spectrum of the manganese ion hybridized degradable polyester of Example 2;

[0016] Figure 4 This is the NMR spectrum of the manganese ion hybridized degradable polyester of Example 3;

[0017] Figure 5 is the NMR spectrum of the degradable polyester of Comparative Example 1;

[0018] Figure 6 This is the NMR spectrum of the degradable polyester containing citric acid in Comparative Example 2;

[0019] Figure 7 is the infrared spectrum of the oligomer before adding the metal citrate in Example 1;

[0020] Figure 8 is the infrared spectrum of the manganese ion hybridized degradable polyester of Example 1;

[0021] Fig. 9is the infrared spectrum of the manganese ion hybrid degradable polyester of Example 2;

[0022] Fig.10 This is the infrared spectrum of the manganese ion hybridized degradable polyester of Example 3;

[0023] Fig.11 is the infrared spectrum of the degradable polyester of Comparative Example 1;

[0024] Fig.12 This is the infrared spectrum of the degradable polyester containing citric acid in Comparative Example 2;

[0025] Fig.13 The metal element test results of the manganese ion hybridized degradable polyester of Examples 1-3;

[0026] Fig.14 This is a summary diagram of the expression promotion rate of ALPL;

[0027] Fig.15 It is a summary diagram of the promotion rate of SPP1 expression;

[0028] Fig.16 It is a summary diagram of Runx2 expression promotion rate;

[0029] Fig.17 This is a summary diagram of the promotion rate of Bglap expression;

[0030] Fig.18 This is a summary diagram of the Col1a1 expression promotion rate. DETAILED DESCRIPTION

[0031] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0033] the term

[0034] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0035] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0036] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0037] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0038] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.

[0039] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0040] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.

[0041] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0042] The first aspect of the present application provides a metal ion hybridized degradable polyester. In one embodiment, the preparation method of the metal ion hybridized degradable polyester comprises the following steps:

[0043] In the presence of a catalyst, the degradable component is polymerized at a temperature of 120° C. to 210° C. for a time of 2 hours to 4 days to obtain a reaction system containing a polymer with a weight average molecular weight of 1000 Dalton to 10000 Dalton, wherein the degradable component comprises a degradable monomer and an initiator, or the degradable component comprises a degradable monomer pair;

[0044] Adding metal citrate into the reaction system, the polymer and the metal citrate continue to react chemically to prepare the soluble metal ion hybridized degradable polyester.

[0045] The metal ion hybridized degradable polyester of the present application is formed by chemically reacting a degradable monomer / initiator, or an oligomer obtained by polymerization of a degradable monomer pair with a metal citrate, and introducing a citric acid structure and a metal ion into the polyester molecular chain. After the citric acid structure is introduced into the polyester molecular chain, the obtained citric acid polyester structure has excellent biocompatibility, and its degradation product citric acid can participate in the tricarboxylic acid cycle of the organism, and is a structure with cell activity. In addition, metal ions can regulate angiogenesis and bone tissue regeneration through various pathways. The metal ion hybridized degradable polyester prepared in the present application can be used as a bone phase filling material, providing a microenvironment that is beneficial to bone health, promoting bone metabolism, mineralization and development, and providing a new choice for highly bioactive bone phase filling materials.

[0046] Optionally, among the degradable monomers and initiators, the degradable monomers include one or more of glycolide, lactide, glycolic acid, lactic acid, caprolactone and p-dioxanone, and the initiators include one or more of diethylene glycol, 1,4-butanediol, 1,6-hexanediol and 1,8-octanediol.

[0047] Optionally, the degradable monomer pair includes one or more of a monomer pair of an alcohol and a polyacid and a monomer pair of an ester and a polyol. The alcohol includes one or more of isosorbide and neopentyl glycol, the ester includes one or more of diphenyl carbonate, butylene succinate, butylene adipate and butylene terephthalate, the polyacid is selected from one or more of citric acid, L-malic acid, succinic acid, 1,5-pentanedioic acid, 1,6-hexanediol, 1,8-octanedioic acid, 1,9-nonanediol and 1,10-decanedioic acid, and the polyol is selected from one or more of 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol and 1,12-dodecanediol.

[0048] Optionally, the catalyst is selected from one or more of tetraethyl titanate, tetrabutyl titanate, tetraisopropyl titanate, boron trifluoride, stannous octoate, tin tetrachloride, stannous oxalate, stannous chloride, organic bismuth catalysts, p-toluenesulfonic acid, butyl stannic acid, p-toluenesulfonic acid, thionyl chloride, 717 type anion exchange resin, sodium methoxide, sodium ethoxide, sodium carbonate, metal oxides and metal chlorides.

[0049] Optionally, the mass of the catalyst accounts for 1% to 5% of the total mass of the degradable component and the metal citrate. For example, the mass of the catalyst accounts for 1%, 2%, 3%, 4%, or 5% of the total mass of the degradable component and the metal citrate.

[0050] Optionally, the mass of the initiator accounts for 0.1% to 5% of the mass of the degradable monomer. For example, the mass of the initiator accounts for 0.1%, 0.5%, 1%, 3%, or 5% of the total mass of the degradable monomer.

[0051] It is understood that the polymerization reaction is carried out in an environment without water or oxygen, for example, in a nitrogen atmosphere.

[0052] Optionally, the polymerization reaction temperature is 120° C. to 200° C. For example, the polymerization reaction temperature is 120° C., 150° C., or 200° C.

[0053] Optionally, the polymerization reaction time is 2 hours to 4 days. For example, the polymerization reaction time is 2 hours, 3 hours, 1 day, 2 days, 3 days, or 4 days.

[0054] Optionally, the reaction pressure of the polymerization reaction is 0-1500 Pa. For example, the reaction pressure of the polymerization reaction is 0Pa, 100Pa, 500Pa, 100Pa, 1500Pa.

[0055] It can be understood that the weight average molecular weight of the polymer in the reaction system obtained by the polymerization reaction of the degradable components includes but is not limited to 1000 Daltons, 5000 Daltons, 8000 Daltons, and 10000 Daltons.

[0056] Adding a metal citrate to the reaction system. Optionally, the metal citrate includes one or more of manganese citrate, sodium citrate, lithium citrate, potassium citrate, ferric citrate, zinc citrate, copper citrate, strontium citrate and cobalt citrate.

[0057] Optionally, the mass ratio of the metal citrate to the degradable component is 1:(3-10). For example, the mass ratio of the metal citrate to the degradable component is 1:3, 1:5, 1:7, or 1:10.

[0058] It is understood that the reaction between the polymer and the metal citrate is carried out in an anhydrous and oxygen-free environment, for example, in a nitrogen atmosphere.

[0059] Optionally, the reaction temperature of the polymer and the metal citrate is 120°C to 210°C. Different from physically mixing the metal citrate and the polymer, at the above temperature, the metal citrate can chemically react with the above 1000 to 10000 Dalton polymer to hybridize and graft the citric acid structure and the metal ion onto the polymer molecular chain. For example, the reaction temperature is 120°C, 150°C, 180°C, 210°C.

[0060] Optionally, the reaction time of the polymer and the metal citrate is 36 h to 72 h. For example, the reaction time is 36 h, 48 h, 60 h, or 72 h.

[0061] Optionally, the reaction pressure of the polymer and the metal citrate is 0-1500 Pa. For example, the reaction pressure is 0 Pa, 100 Pa, 500 Pa, 100 Pa, 1500 Pa.

[0062] The above preparation method can prepare a metal ion hybridized degradable polyester with a weight average molecular weight of 5000 Dalton to 20000 Dalton. For example, the weight average molecular weight is 5000 Dalton, 10000 Dalton, 15000 Dalton, and 20000 Dalton. In addition, the prepared metal ion hybridized degradable polyester is soluble and can be dissolved in a good solvent. The good solvent includes one or more of chloroform, dichloromethane, dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0063] A second aspect of the present application provides a metal ion hybridized degradable polyester. In one embodiment, the metal ion hybridized degradable polyester is prepared by the preparation method as described above.

[0064] Optionally, the weight average molecular weight of the metal ion hybridized degradable polyester is 5000 Daltons to 20000 Daltons.

[0065] Optionally, the metal ion hybridized degradable polyester is in granular form. Optionally, the particle size of the degradable polyester is 0.1µm to 50µm. For example, the particle size of the degradable polyester is 0.1µm, 1µm, 5µm, 10µm, 20µm, and 50µm. The degradable polyester of the above particle size can be obtained by ball milling and sieving.

[0066] A third aspect of the present application provides a bone phase filling material. In one embodiment, the bone phase filling material includes the degradable polyester as described above.

[0067] The above-mentioned bone filling material can be injected to fill the bones to achieve the effects of repair, shaping, anti-aging, etc. Optionally, the bone filling material also includes excipients. Optionally, the mass ratio of the degradable polyester to the excipient is 1: (0.1~5). For example, the mass ratio of the degradable polyester to the excipient is 1:0.1, 1:1, 1:2, 1:3, 1:4, 1:5. The dosage form of the bone filling material can be a lyophilized powder or a gel. Among them, the lyophilized powder can be obtained by mixing the degradable polyester, the excipient and the water for injection and then freeze-drying it, or the degradable polyester can be mixed with the excipient to prepare the gel, and then the gel can be freeze-dried. The freeze-drying process can be carried out in a freeze dryer. Optionally, the freeze-drying time is 20h~48h, including but not limited to 20h, 24h, and 28h.

[0068] In one example, degradable polyester, excipients and water for injection are added to a vial, which is half-capped and placed in a freeze dryer, and freeze-dried for 24 hours to obtain freeze-dried powder of degradable polyester.

[0069] In one example, the degradable polyester and the auxiliary material are mixed and loaded into a syringe with a Luer connector to obtain the degradable polyester gel.

[0070] Optionally, the excipients include one or more of carboxymethyl cellulose, mannitol, collagen and hyaluronic acid.

[0071] Optionally, the auxiliary material includes carboxymethyl cellulose. Optionally, the mass ratio of the degradable polyester to the carboxymethyl cellulose is 1:(2-3). Including but not limited to 1:2, 1:2.5, 1:3. For example, 50 mg of degradable polyester and 150 mg of carboxymethyl cellulose are mixed to prepare a gel.

[0072] Optionally, the excipients include carboxymethyl cellulose and mannitol. Optionally, the mass ratio of the degradable polyester, carboxymethyl cellulose and mannitol is 1: (0.1-2.5): (0.1-1). Including but not limited to 1: (0.5-1): (0.5-1). For example, 150 mg of degradable polyester, 90 mg of carboxymethyl cellulose, 127.5 mg of mannitol and 5 mL of water for injection are mixed, half-capped and placed in a freeze dryer, and freeze-dried for 24 hours to obtain a freeze-dried powder of the degradable polyester.

[0073] Optionally, the excipients include carboxymethyl cellulose, mannitol and collagen. Optionally, the mass ratio of the degradable polyester, mannitol and collagen is 1: (0.1-2.5): (0.1-1): (0.1-1.5). Including but not limited to 1: (0.3-1): (0.2-1): (0.5-1). For example, 150 mg of degradable polyester, 50 mg of carboxymethyl cellulose, 40 mg of collagen, 127.5 mg of mannitol and 5 ml of water for injection are mixed, half-capped and placed in a freeze dryer, and freeze-dried for 24 hours to obtain a freeze-dried powder of degradable polyester.

[0074] Optionally, the auxiliary material includes hyaluronic acid. Optionally, the mass ratio of the degradable polyester to the hyaluronic acid is 1:(0.1-2), including but not limited to 1:0.1, 1:0.5, 1:1, 1:2.

[0075] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0076] The weight average molecular weight of the polymer was characterized by dissolving the polymer in CHCl3 and using gel permeation chromatography (GPC, Waters 1515).

[0077] Example 1

[0078] This embodiment provides a biodegradable polyester and a preparation method thereof, the steps are as follows:

[0079] Step 1. In an anhydrous and oxygen-free environment, 5.83 g of lactide, 0.52 g of glycolide, 0.01 g of diethylene glycol and 0.2 g of stannous octoate are added to a stirred two-necked flask, nitrogen is introduced into the two-necked flask, and the flask is placed in an oil bath. Under a nitrogen atmosphere, the oil bath is heated to 150° C., and the pressure in the flask is 0.1 MPa. After reacting for 3 hours, a reaction system containing oligomers is obtained. A trace amount of the obtained oligomers is separated from the reaction system, and its weight-average molecular weight is tested to be 2000 Daltons.

[0080] Step 2: Add 0.64 g of manganese citrate to the reaction system containing the oligomer, and at the same time raise the temperature of the oil bath to 180°C. At this time, the pressure in the bottle is 0.1 MPa. After reacting for 48 hours, pour out the reaction mixture while hot, dissolve it with dichloromethane after cooling, and filter it after precipitation in ethanol to obtain a manganese ion hybridized biodegradable polyester. The weight average molecular weight is tested to be 10,500 Daltons.

[0081] Example 2

[0082] This embodiment provides a biodegradable polyester and a preparation method thereof, the steps are as follows:

[0083] Step 1 is the same as in Example 1.

[0084] Step 2: Add 1.27 g of manganese citrate to the reaction system containing the oligomer, and at the same time raise the temperature of the oil bath to 180°C. At this time, the pressure in the bottle is 0.1 MPa. After reacting for 48 hours, pour out the reaction mixture while hot, dissolve it with dichloromethane after cooling, and filter it after precipitation in ethanol to obtain a manganese ion hybridized biodegradable polyester. The weight average molecular weight is tested to be 15,000 Daltons.

[0085] Example 3

[0086] This embodiment provides a biodegradable polyester and a preparation method thereof, the steps are as follows:

[0087] Step 1 is the same as in Example 1.

[0088] Step 2: Add 1.91 g of manganese citrate to the reaction system containing the oligomer, and at the same time raise the temperature of the oil bath to 180°C. At this time, the pressure in the bottle is 0.1 MPa. After reacting for 48 hours, pour out the reaction mixture while hot, dissolve it with dichloromethane after cooling, and filter it after precipitation in ethanol to obtain a manganese ion hybridized biodegradable polyester. The weight average molecular weight is tested to be 18,000 Daltons.

[0089] Comparative Example 1

[0090] This comparative example provides a biodegradable polyester and a preparation method thereof, the steps are as follows:

[0091] Step 1. In an anhydrous and oxygen-free environment, 5.83 g of lactide, 0.52 g of glycolide, 0.01 g of diethylene glycol and 0.2 g of stannous octoate are added to a stirred two-necked flask, nitrogen is introduced into the two-necked flask, and the flask is placed in an oil bath. Under a nitrogen atmosphere, the oil bath is heated to 150° C., and the pressure in the flask is 0.1 MPa. After reacting for 3 hours, the temperature of the oil bath is raised to 180° C., and the pressure in the bottle is 0.1 MPa. After reacting for 48 hours, the reaction mixture is poured out while hot, dissolved in dichloromethane after cooling, and precipitated in ethanol. The degradable polyester is filtered to obtain a weight-average molecular weight of 10,000 Daltons.

[0092] Comparative Example 2

[0093] This comparative example provides a biodegradable polyester and a preparation method thereof, the steps are as follows:

[0094] Step 1 is the same as in Example 1.

[0095] Step 2: Add 0.64 g of citric acid to the reaction system containing the oligomer, and at the same time raise the temperature of the oil bath to 180°C. At this time, the pressure in the bottle is 0.1 MPa. After reacting for 48 hours, pour out the reaction mixture while hot, dissolve it in dichloromethane and precipitate it in ethanol to obtain a degradable polyester containing citric acid. The weight average molecular weight is tested to be 12,000 Daltons.

[0096] Comparative Example 3

[0097] This comparative example provides a preparation method, the steps are as follows:

[0098] In an anhydrous and oxygen-free environment, 5.83 g of lactide, 0.52 g of glycolide, 0.01 g of diethylene glycol, 0.64 g of manganese citrate and 0.2 g of stannous octoate were added to a stirred two-necked flask, nitrogen was introduced into the two-necked flask, and the flask was placed in an oil bath. Under a nitrogen atmosphere, the oil bath was heated to 150°C, and the pressure in the flask was 0.1 MPa. After reacting for 3 hours, the temperature of the oil bath was raised to 180°C, and the pressure in the flask was 0.1 MPa. After reacting for 48 hours, the reaction mixture was poured out while hot, dissolved in dichloromethane after cooling and precipitated in ethanol, and no solid product was obtained, which proved that the addition of manganese citrate in the early stage of the polymerization reaction affected the polymerization reaction and made it difficult to obtain a polyester product.

[0099] Comparative Example 4

[0100] This comparative example provides a method for preparing a degradable polyester composite material by combining a citric acid-based degradable polyester prepolymer and a metal ion compound, and the steps are as follows:

[0101] 0.1 mol each of citric acid, L-malic acid, succinic acid and 0.17 mol of glycerol were added into a two-necked flask, and reacted at 150° C. for 1 hour under nitrogen protection to obtain a prepolymer, which was then dissolved in dioxane.

[0102] The prepolymer and manganese citrate were blended in a mass ratio of 70:30 and placed in a Teflon mold. The solvent was evaporated and then placed in an oven for heating and reaction for 48 hours to obtain a bulk cross-linked polyester composite containing metal ions.

[0103] Test Example 1

[0104] Take appropriate amounts of the manganese ion hybridized degradable polyester obtained in Example 1 and the bulk cross-linked metal ion-containing polyester complex obtained in Comparative Example 4, and try to dissolve them with solvents such as dioxane, chloroform, dichloromethane, dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), respectively. It was found that the manganese ion hybridized degradable polyester obtained in Example 1 was soluble in chloroform, dichloromethane, DMF and DMSO, while the bulk cross-linked metal ion-containing polyester complex obtained in Comparative Example 4 could only swell but could not be dissolved in any of the several solvents. Compared to bulk cross-linked complexes that can only be shaped before post-cross-linking, the manganese ion hybridized degradable polyester obtained in Example 1 can be dissolved in a good solvent, can be further shaped, and can also be prepared into microspheres by an emulsion method, which has a wider range of application scenarios.

[0105] Test Example 2

[0106] Take appropriate amounts of the oligomer before adding citric acid metal salt of Example 1, the manganese ion hybridized degradable polyester of Examples 1 to 3, the degradable polyester of Comparative Example 1, and the degradable polyester containing citric acid of Comparative Example 2, and dissolve them in CDCl3, and perform nuclear magnetic resonance testing using a nuclear magnetic resonance spectrometer (300 MHz, AV3000 Bruker, Germany). The results are shown in Table 1. Figures 1 to 6 It can be seen that the NMR spectra before and after adding manganese citrate in the comparative example ( Figure 1 and Figure 2 ), after adding manganese citrate, a new peak appeared at 2.0-2.5ppm, which should be attributed to the hydrogen on -CH2- in citric acid, indicating that manganese citrate was successfully introduced. Figure 3 and Figure 4 A new peak at 2.0-2.5 ppm can also be seen in the graph. The NMR image of pure poly(lactide-glycolide) (PLGA) obtained in Comparative Example 1 ( Figure 5 ) No peak at 2.0-2.5ppm was observed; in Comparative Example 2, PLGA oligomer ( Figure 1 ), the new peak is at 2.5-3.0ppm, which is similar to Figure 3 and Figure 4 are different, reflecting the chemical shift change of -CH2- in pure citric acid and metal citrate.

[0107] Test Example 3

[0108] Take appropriate amounts of the oligomer before adding citric acid metal salt of Example 1, the manganese ion hybridized degradable polyester of Examples 1 to 3, the degradable polyester of Comparative Examples 1-2, and the degradable polyester containing citric acid of Comparative Example 2, respectively, and mix them with potassium bromide powder and press them into tablets. Put the potassium bromide tablets with the samples into an infrared spectrometer for testing to obtain infrared spectra of the samples, as shown in FIG. Figures 7 to 12 The infrared spectra of all samples show a peak at 1750cm -1The strong ester bond (-COO-) absorption peak near 2950cm -1 The absorption peaks of methyl and methylene on the left and right further prove that the polyester is successfully synthesized; compared with the oligomer before adding citrate metal salt ( Figure 7 ) and high molecular weight PLGA ( Fig.11 ) is compared with the infrared spectrum of the polyester containing manganese citrate ( Figure 8-10 ) at 3500cm -1 There is a larger absorption peak, which can be attributed to the absorption peak of the carboxyl group, proving the successful introduction of manganese citrate. Figure 8-10 ) compared to polyester containing citric acid ( Fig.12 ) at 3500cm -1 The absorption peak at is stronger, indicating that the presence of metal ions will reduce the intensity of the carboxyl absorption peak.

[0109] Test Example 4

[0110] Take appropriate amounts of the manganese ion hybridized degradable polyesters of Examples 1 to 3 and digest them in digestion tanks to obtain test solutions; prepare standard solutions of different concentrations of manganese elements, measure the spectral intensity of manganese elements, and draw a standard curve. Test the spectral intensity of manganese elements in the test solutions, calculate the concentration of manganese elements from the standard curve, and the results are shown in Fig.13 .Depend on Fig.13 It can be seen that as the amount of manganese citrate added increases, the manganese ion content of the polyester in Example 2 increases compared to the polyester obtained in Example 1; however, excessive addition of manganese citrate instead leads to a decrease in the manganese ion content in the final product (Example 3).

[0111] Test Example 5

[0112] q-PCR detection: osteogenic activity and ability to promote collagen release: healthy zebrafish 5 days after fertilization were selected, and a blank control group (fish embryo culture medium) and a test group (the manganese ion hybridized degradable polyester of Example 1-Example 3 and the degradable polyester of Comparative Example 1-2 were mixed with collagen respectively to obtain a gel). After 14 days of co-culture, mRNA extraction and cDNA synthesis were performed, and then real-time PCR was performed to test gene expression. The expression promotion rates of alkaline phosphatase (ALPL), secretory phosphoprotein 1 (SPP1), Runt-related transcription factor 2 (Runx2), bone γ-carboxyglutamate protein (Bglap) and type I collagen α1 chain (Col1a1) were calculated and detected. The data are summarized in Figures 14 to 18 .

[0113] Among them, alkaline phosphatase (ALPL) is an enzyme that plays a key role in the mineralization of bones and teeth, and its high level of expression is usually associated with bone growth and repair. Secretory phosphoprotein 1 (SPP1), also known as osteopontin (OPN), plays a regulatory role in bone formation and remodeling, and is associated with cell adhesion, migration and differentiation. Runt-related transcription factor 2 (Runx2) is a core transcription factor that regulates bone formation and osteoblast differentiation, and its high level of expression is closely related to osteoblast differentiation and maturation. Bone γ-carboxyglutamate protein (BGLAP), also known as osteocalcin, is one of the main non-collagenous proteins of bone matrix. It participates in the bone mineralization process and is related to bone strength and toughness. Type I collagen α1 chain (Col1a1) is an important component of encoding type I collagen, which is the main structural protein of bone and connective tissue and is essential for maintaining bone strength and stability.

[0114] Depend on Figures 14 to 18 It can be seen that the test substance groups of Examples 1 to 3 can induce high expression of alkaline phosphatase (ALPL), secretory phosphoprotein 1 (SPP1), Runt-related transcription factor 2 (Runx2), bone γ-carboxyglutamate protein (BGLAP) and type I collagen α1 chain (Col1a1), indicating the active state of the degradable polyesters of Examples 1 to 3 in bone metabolism, mineralization and bone development.

[0115] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0116] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a metal ion hybridized degradable polyester, characterized in that: The following steps are involved: In the presence of a catalyst, the degradable component is polymerized at a temperature of 120° C. to 210° C. for a time of 2 hours to 4 days to obtain a reaction system containing a polymer with a weight average molecular weight of 1000 Dalton to 10000 Dalton, wherein the degradable component comprises a degradable monomer and an initiator, or the degradable component comprises a degradable monomer pair; Adding metal citrate into the reaction system, the polymer and the metal citrate continue to react chemically to prepare the soluble metal ion hybridized degradable polyester.

2. The method for preparing the metal ion hybridized degradable polyester according to claim 1, characterized in that: The metal citrate includes one or more of manganese citrate, sodium citrate, lithium citrate, potassium citrate, ferric citrate, zinc citrate, copper citrate, strontium citrate and cobalt citrate.

3. The method for preparing the metal ion hybridized degradable polyester according to claim 1, characterized in that: The mass ratio of the metal citrate to the degradable component is 1:(3-10).

4. The method for preparing the metal ion hybridized degradable polyester according to claim 1, characterized in that: The conditions for the chemical reaction between the polymer and the metal citrate include at least one of the following: (1) The reaction temperature is 120℃~210℃; (2) The reaction time is 36h~72h; (3) The reaction pressure is 0~1500Pa.

5. The method for preparing the metal ion hybridized degradable polyester according to claim 1, characterized in that: Includes at least one of the following features: (1) The mass of the catalyst accounts for 1% to 5% of the total mass of the degradable component and the metal citrate; (2) The catalyst is selected from one or more of tetraethyl titanate, tetrabutyl titanate, tetraisopropyl titanate, boron trifluoride, stannous octoate, tin tetrachloride, stannous oxalate, stannous chloride, organic bismuth catalyst, p-toluenesulfonic acid, butyl stannic acid, p-toluenesulfonic acid, thionyl chloride, 717 type anion exchange resin, sodium methoxide, sodium ethoxide, sodium carbonate, metal oxides and metal chlorides.

6. The method for preparing the metal ion hybridized degradable polyester according to any one of claims 1 to 5, characterized in that: Includes at least one of the following features: (1) The degradable monomers include one or more of glycolide, lactide, glycolic acid, lactic acid, caprolactone and p-dioxanone; (2) The initiator includes one or more of diethylene glycol, 1,4-butanediol, 1,6-hexanediol and 1,8-octanediol; (3) The degradable monomer pair includes one or more of a monomer pair of an alcohol and a polyacid and a monomer pair of an ester and a polyol, the alcohol includes one or more of isosorbide and neopentyl glycol, the ester includes one or more of diphenyl carbonate, butylene succinate, butylene adipate and butylene terephthalate, the polyacid is selected from one or more of citric acid, L-malic acid, succinic acid, 1,5-pentanedioic acid, 1,6-hexanedioic acid, 1,8-octanedioic acid, 1,9-nonanedioic acid and 1,10-decanedioic acid, and the polyol is selected from one or more of 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol and 1,12-dodecanediol.

7. The method for preparing the metal ion hybridized degradable polyester according to any one of claims 1 to 5, characterized in that: The mass of the initiator accounts for 0.1% to 5% of the mass of the degradable monomer.

8. The method for preparing the metal ion hybridized degradable polyester according to any one of claims 1 to 5, characterized in that: Includes at least one of the following features: (1) The polymerization reaction temperature is 120°C to 200°C; (2) The polymerization reaction time is 2h~3h; (3) The reaction pressure of the polymerization reaction is 0~1500Pa.

9. A metal ion hybridized degradable polyester, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.

10. A bone filling material, characterized in that: The invention comprises the metal ion hybridized degradable polyester as claimed in claim 9.